Networking in Supply Chain Integration: Implementing RosettaNet Payments in the Finnish ITC–Sector - Jokinen, Juho (My University, 2004)
This thesis is a case study of networking in supply-chain integration in the Finnish Information Technology and Communications (ITC) –sector. The empirical part of the thesis was conducted in the autumn of 2003. The study explores the networking where the actors of a supply chain together with supporting businesses take part to enhance their supply chain relationships. Thus the studied phenomenon crosses traditional supply chain relationships to form a larger network in and around a supply chain. The theoretical framework combines networking-, supply chain-, and alliance making –theories. A specific role is given to the financial supply chain as a new phenomenon, and the bank as a new actor in serving supply chain integration. The study explores networking in supply chain integration through the case of a new standard launched in supply chain integration: RosettaNet payments. The aim of the RosettaNet Payment Program is to automate accounts receivables, and payment initiation, and allow the tracking of payments in the payment processes of supply chains. The methodology is qualitative with theme interviews of nine manager level employees. The interviewees are from both supporting businesses, and from within the supply chain. The businesses include large information technology companies, software producers, operators and consultants. Exploring a phenomenon of networking through the appearance of a new service will lead the study to propose roles for the industries in the supposed network, to propose the qualities of networks in supply chain integration, and to propose a number of possible forms networks take. Therefore, the contribution of the study is an explanation of what kind of networks form, when a new product or service is implemented in a supply chain. Further, the study proposes a definition for the financial supply chain and discusses the possibility of making alliances in this sector. The study was conducted by appointment of Nordea Bank Finland.
Keywords: Networking; supply–chain management; financial supply chain; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Liiketoimintakonsultoinnin koulutusohjelma|